PERBEDAAN SISA MAKANAN PASIEN BERDASARKAN TINGKAT PENGETAHUAN DIET RENDAH GARAM DAN PERSEPSI CITA RASA DI RSUD WANGAYA KOTA DENPASAR - Nengah Suryaningsih; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
The remaining food percentage is a simple indicator to evaluate the success of hospital nutritional services. One of the factors influencing is the level of knowledge of low salt diets and the perception of taste. The amount of food remaining will have an impact on patient nutritional status and patient recovery. Based on hospital nutritional guidelines, Standard indicator of food waste ≤ 20%. The purpose of this research is to find out about the Difference Of Patient Food Waste Based On Knowledge Levels Of Low Salt Diets And Flavor Perception At RSUD Wangaya Denpasar City. This research draft is cross sectional with a total of 62 inpatient samples. Food waste data is obtained by food weighing method. The level of knowledge of low salt diets and the perception of taste collected with questionnaires. The results of the research found that the patient's waste were classified as little is about 33 persons (53,2%), the level of knowledge is good which is about 58 persons (93,55%), and the perception of taste is in the good category which is about 56 persons (90,3%). Research results after the chi square test show no significant difference between foods waste with low salt diet knowledge levels (p=0,082). While analyzed difference food leftovers with taste perception showed (p=0,000) that means there is a significant difference.Keywords : Food Waste, Knowledge Levels of Low Salt Diets, Flavour Perception.